FORMALIZED EVALUATION OF SCENARIO DEVELOPMENT OF THE NATIONAL ECONOMY IN TERMS OF PENETRATION OF BLOCKCHAIN TECHNOLOGIES IN THE FINANCIAL SECTOR - M. R. Safiullin; A. A. Abdukaeva; L. A. Elshin; M. V. Savushkin (Вестник университета)
In the coming years, blockchain technologies may become one of the breakthrough innovations in the financial sector of the economy, optimizing and simplifying transaction operations in a number of areas, reducing their cost. Having a very significant potential for transforming the established algorithms for the interaction of financial market participants, it is important to understand what are the boundaries of these changes, what new opportunities are presented by blockchain technologies and, finally, what are the expected consequences for the development of the financial sector itself and the other sectors of the national economic system associated with it. In this regard, important and urgent task is to minimize risks for financial and other organizations in the face of impending opportunities and threats under the pressure of the process of integrating blockchain platforms into the economic environment. This research is devoted to the solution of the issues posed. The most important component of the paper is the proposed methodological toolkit, which allows you to identify in a formalized form the patterns and relationships between the level of penetration of blockchain technologies into the financial environment and the dynamics of gross domestic product ( GDP).